A comparison of single-entry and multiple-entry casing impingement manifolds for active thermal tip clearance control - Dhopade, P; Kirollos, B; Ireland, P; Lewis, L (MDPI, 2021)
In this paper, we compare using computational fluid dynamics the aero-thermal performance of two candidate casing manifolds for supplying an impingement-actuated active tip clearance control system for an aero-engine high-pressure turbine. The two geometries are (a) single-entry: An annular manifold fed at one circumferential location; (b) multiple-entry: A casing manifold split into four annular sectors, with each sector supplied separately from an annular ring main. Both the single-entry and multiple-entry systems analysed in this paper are idealised versions of active clearance control systems in current production engines. Aero-thermal performance is quantitatively assessed on the basis of the heat transfer coefficient distribution, driving temperature difference for heat transfer between the jet and casing wall and total pressure loss within the high-pressure turbine active clearance control system. We predict that the mean heat transfer coefficient (defined with respect to the inlet temperature and local wall temperature) of the single-entry active clearance control system is 77% greater than the multiple-entry system, primarily because the coolant in the multiple-entry case picks up approximately 40 K of temperature from the ring main walls, and secondarily because the average jet Reynolds number of impingement holes in the single-entry system is 1.2 times greater than in the multiple-entry system. The multiple-entry system exhibits many local hot and cold spots, depending on the position of the transfer boxes, while the single-entry case has a more predictable aero-thermal field across the system. The multiple-entry feed system uses an average of 20% of the total available pressure drop, while the feed system for the single-entry geometry uses only 2% of the total available pressure drop. From the aero-thermal results of this computational study, and in consideration of holistic aero-engine design factors, we conclude that a single-entry system is closer to an optimal solution than a multiple-entry system.